Epidemiological profile of snakebites in Rio de Janeiro, Brazil, 2001-2006 - Machado, C. (2012)
The authors thank Dr. Antonio Joaquim Werneck de Castro and Luis Eduardo Ribeiro da Cunha of Vital Brazil Institute for providing the necessary facilities, and are also grateful to post-graduation program in Information and Communication in Health (PPGICS) of Fiocruz